Tennis ground strokes from a bird's eye view - a estimate of angular momentum about the longitudinal body axis - Hannappel, S.; Eckardt, N.; Fischer, S.; Kibele, A. (ISBS Proceedings Archive (Michigan), 2017)
In this paper, a simple 2D video method will be outlined to estimate the angular momentum about the longitudinal body axis in tennis ground strokes from the base line. From a bird`s eye view, ground strokes of 19 young male experienced tennis players with two different skill levels were analyzed when returning balls released from a ball machine with three different ball frequencies. The angle between the shoulder axis and the base line was used as an estimate for the angular momentum about the longitudinal body axis. A validation procedure with a fully automated 3D motion capture system as adopted to evaluate the error involved in the 2D motion analysis. The results of this study show that for forehand and backhand strokes advanced young tennis players show consistently larger shoulder-baseline angles across all ball frequencies than players with a lower skill level.